Pengembangan Media 3D Tipe Model Wayang Kancil dan Buaya dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar Islam - Muhammad Majdi; Sandy Aulia Rahman; Muhammad Humaidi (AN NUR: Jurnal Studi Islam, 2022)
This research aimed to determine the development of 3-dimensional (3D) media in the form of wayang mouse deer and crocodiles in Indonesian language learning, namely fable stories at the SD/MI level with several principles of analysis, namely advantages, disadvantages and aspects that were highlighted. This research method used a qualitative approach. The results showed that the development of 3D media types of wayang kancil and crocodile models in learning Indonesian SD/MI had gone well according to the steps which consisted of the introduction, core, and closing sections. While the advantages include a) substituting real objects, thereby providing direct experience, b) presenting material concretely and avoiding verbalism, and c) clear flow. Finally, the activities highlighted in this study were aspects of attitude and communication.